Influence of Products Mix of Samsung Galaxy Mobile onConsumer loyalty in the UNPAD Student Community - Kurniawan, Ryan (International Journal of Psychosocial Rehabilitation, 2020)
The product mix is one of the considerations that influence consumers in product selection. Based on these considerations, consumers have the nature of voters, because that company must be able to read consumer behavior to be able to get loyal consumers. For companies to be able to compete in business, these loyal consumers strengthen the company's position. This condition makes the author interested in researching the mix of products offered by Samsung Galaxy Mobile. Whether it has an influence on consumers, entitled "The Influence of Mixing Samsung Galaxy Mobile Products on Consumer Loyalty to the UNPAD Student Community." This study processed 100 questionnaires from UNPAD students randomly. The method used in this study is descriptive. The research method describes the actual conditions that have been known through data collection, which is then analyzed so that ultimately, a conclusion is produced. The results showed that respondents' responses to the mix of Samsung Galaxy Mobile Products obtained an average value of 4.41, which stated very well. While respondents' responses to loyalty to Samsung Galaxy Mobile products are quite high, indicated by an average value of 4.07.